PENILAIAN HARGA SAHAM PERUSAHAAN PEMBIAYAAN DI BURSA EFEK INDONESIA - Kim Hong; Fakhruddin Nasution (Media Riset Akuntansi, Auditing & Informasi, 2012)
The purpose of multi finance companies’ stock price valuation is to know their intrinsic values by performing fundamental analysis using dividend discount model, free cash flow to the firm model, free cash flow to equity model, and residual income model. Research data uses secondary data in the period of 2006-2010 which consists of Indonesian Stock Price Composite Index (IHSG), and multi finance companies’ stock prices taken from Yahoo Finance; multi finance companies’ financial statements taken from Indonesian Stock Exchange (BEI) reports; multi finance industry data taken from Bapepam-LK. As a result of research, stock of ADMF is fair valued by using the analysis of dividenddiscount model; undervalued by using the analysis of free cash flow to the firm and free cash flow to equity models; overvalued by using the analysis of residual income model. Stock of BFIN is undervalued by using the analysis of dividend discount, free cash flow to the firm, and free cash flow to equity models; overvalued by using the analysis of residual income model. Stock of MFIN is overvalued by using the analysis of dividend discountand residual income models; undervalued by using the analysis of free cash flow to the firm and free cash flow to equity models. Statistic t-test shows that there are no significant differences to value stock prices using dividend discount, free cash flow to the firm, free cash flow to equity, and residual income models, therefore investment analyst or investor may use one of the chosen stock price valuation model.Keywords: Multi finance companies, Fundamental analysis, Stock price valuation model, Intrinsic value, Required return, Investment risk